Expressive Illocutionary Acts in the Ken Dedes Webtoon: A Digital Pragmatic Perspective - Putu Vania Maharani Suastha, (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This study examines the use of expressive illocutionary acts in the Ken Dedes Webtoon, focusing on their role in portraying emotions, attitudes, and social relationships between characters. Using Yule's (1996) speech act theory and a qualitative descriptive approach, the study analyzes five types of expressive acts—gratitude, plea for mercy, anger, surprise, and sarcasm—through the verbal and visual expressions in dialogues. The results reveal that expressions of gratitude reflect respect and politeness norms, contributing to harmonious social relationships. Pleas for mercy highlight hierarchical relationships, illustrating fear and humility as mechanisms to seek forgiveness. Anger expressions emphasize dissatisfaction and interpersonal conflict, while surprise adds dramatic tension by depicting characters’ internal struggles in unexpected situations. Lastly, sarcasm conveys disappointment and critiques through subtle rhetoric, underscoring power dynamics and cultural expectations in hierarchical societies.Overall, the expressive illocutionary acts in Ken Dedes enhance the story's dramatic elements while reflecting Javanese cultural values, such as hierarchy, politeness, and social responsibility. This study contributes to digital pragmatics by demonstrating how Webtoons serve as modern platforms for representing and reinterpreting cultural heritage, making it relevant for the digital generation.